Clinical profile of COVID-19 patients and factors impacting mortality in a rural tertiary care center of Solapur - Nirmal Taparia (Asian Journal of Medical Sciences, 2024)
Background: A retrospective and cohort study was conducted in our center to study the parameters among surviving and non-surviving patients that have a significant impact on in hospital mortality. Along with this, demographic and clinical profile was also studied. Aims and Objectives: The aim of this study was to evaluate clinical profile of COVID-19 patients and factors impacting mortality. Materials and Methods: The present study is a single-center, retrospective, and cohort study done on COVID-19 positive (by real-time polymerase chain reaction) patients admitted between May 2019 and June 2021 in the intensive care unit (ICU). Of the total 1694 patients, 422 required ICU treatment and the remaining 1272 patients were treated in wards and rooms and discharged home. The analysis was based on demographic, clinical, associated comorbidities, laboratory and radiological data, and treatment modalities used. Outcome data were analyzed by regression analysis and the Kaplan–Meir survival plot was used to calculate mortality trend. Results: Of the 422 patients, 158 (37.4%) died and 264 (62.6%) survived. Males predominated with 297/422 (70.4%). ICU admissions comprised 115/158 (72.8%) of the total deaths. Fever (88%), dyspnea (78.48), and cough (67.1%) were the most common symptoms in non-survival group. Hypertension (43.7%) and diabetes (37.3%) were the most common comorbidities. High oxygen (>10 L/min) (P<0.0001), invasive ventilation (P<0.0001), noradrenaline infusion P<0.0001), renal replacement therapy (P<0.0001) and tocilizumab requirement (P<0.0001), procalcitonin (P<0.009) and interleukin-6 (P<0.004) acute respiratory distress syndrome (ARDS) with septic shock, and multiorgan failure (P<0.0001), all indicated higher risk of death. Conclusion: Mortality was 37.4% in our study. Elderly age (>60 years), high serum ferritin (>931.9), and severe disease with a high resolution computed tomography score (>15), ARDS with septic complications requiring invasive ventilation and vasopressor support, are associated with increased mortality in these patients.